Pengembangan Media Pembelajaran Komik Digital Berbantuan Aplikasi Canva pada Materi Cahaya dan Sifatnya di Kelas V Sekolah Dasar Negeri 108306 Tanjung Garbus - Rini Nanda Hanifa; Nuri Ramadhan; Layil Safitri (Medan Resource Center, 2025)
This study addresses the limited availability of digital learning media and students’ difficulties in comprehending the abstract concept of light by developing a digital comic–based learning medium assisted by the Canva application for fifth-grade students at State Elementary School 108306 Tanjung Garbus. The research aims to examine the feasibility and effectiveness of the developed digital comic in supporting science learning on the topic of light and its properties. Employing a Research and Development approach, the study adopted the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The developed media integrates conceptual explanations, character-based dialogues, narration audio, and visually engaging illustrations to enhance students’ conceptual understanding. The research subjects consisted of twenty-five students and two expert validators. Data were collected through expert validation questionnaires and a One Group Pretest–Posttest design to measure learning effectiveness. The findings reveal a very high level of feasibility, with validation scores of one hundred percent from media experts, ninety-eight percent from material experts and teachers, and eighty-seven percent from students. Overall, the digital comic learning media is proven to be pedagogically effective and appropriate for classroom implementation, contributing to improved understanding of scientific concepts and supporting innovative digital instruction in elementary education.